2020
DOI: 10.1186/s40364-020-00201-8
|View full text |Cite
|
Sign up to set email alerts
|

Roles of HMGB1 in regulating myeloid-derived suppressor cells in the tumor microenvironment

Abstract: Myeloid-derived suppressor cells (MDSCs) are notable contributors to the immunosuppressive tumor microenvironment (TME) and are closely associated with tumor progression; in addition, MDSCs are present in most patients with cancer. However, the molecular mechanisms that regulate MDSCs in the etiopathogenesis of human tumor immunity remain unclear. The secreted alarmin high mobility group box 1 (HMGB1) is a proinflammatory factor and inducer of many inflammatory molecules during MDSC development. In this review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 74 publications
0
22
0
Order By: Relevance
“…The main alarmin, HMGB1, released by pyroptotic cells, could promote tumor cell survival, which largely suggests that HMGB1 drives the accumulation of MDSCs by inducing autophagy, thereby maintaining MDSC viability. 268 , 269 , 270 In addition, HMGB1 also enhances the immune suppression of MDSCs by promoting their differentiation from bone marrow progenitor cells and the suppressive activity on antigen‐driven activation of CD4 + and CD8 + T cells. 271 Moreover, HMGB1 also increases MDSC‐mediated IL‐10 production, enhancing crosstalk between MDSCs and macrophages, and down‐regulating L‐selection on T cells to perturb their location to lymph nodes.…”
Section: Pyroptosis and Tumor Immune Microenvironmentmentioning
confidence: 99%
“…The main alarmin, HMGB1, released by pyroptotic cells, could promote tumor cell survival, which largely suggests that HMGB1 drives the accumulation of MDSCs by inducing autophagy, thereby maintaining MDSC viability. 268 , 269 , 270 In addition, HMGB1 also enhances the immune suppression of MDSCs by promoting their differentiation from bone marrow progenitor cells and the suppressive activity on antigen‐driven activation of CD4 + and CD8 + T cells. 271 Moreover, HMGB1 also increases MDSC‐mediated IL‐10 production, enhancing crosstalk between MDSCs and macrophages, and down‐regulating L‐selection on T cells to perturb their location to lymph nodes.…”
Section: Pyroptosis and Tumor Immune Microenvironmentmentioning
confidence: 99%
“…Based on their origin, tissue localization, and mechanism of immune suppression, MDSCs can be divided into monocytic MDSCs and polymorphonuclear MDSCs. They exhibit immunosuppressive capability by inhibiting other immune cells in a context-dependent manner [9,10]. Besides, NK cells and DCs are thought to participate in potent anti-tumor immune response, but various immunosuppressive factors tend to restrain their abilities and drive them into pro-tumor phenotypes [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…However, we inferred that HMGBs were inclined to induce overall immunosuppression in the TIME, since we found that they had uniformly positive correlations with the infiltration of Th2 cells and MDSCs in pancancer. Indeed, interactions between HMGB1 and its receptors are critical for the differentiation and activation of MDSCs (Jin et al, 2020) and Tregs (Wild et al, 2012) and the upregulation PD-L1 in the TIME (Wang et al, 2019). Besides, it was evident that HMGB1 could induce a dominance of Th2-type response in inflammation (Ma et al, 2015).…”
Section: Discussionmentioning
confidence: 99%